Socialization and Training on Processing LDPE (Low-Density Polypropylene) Plastic Waste into Paving Blocks - Agustinur, Satya Cantika; Basmalah, Mazaya; Novianti, Eni; Lestari, Emilia Dwi; Martila, Lenny Intan; Putri, Rahadian Dwi Oktavia; Yantidewi, Meta; Deta, Utama Alan (Mitra Edukasi dan Publikasi, 2023)
The increasing amount of waste in Indonesia, especially in Surabaya, is a severe problem that must be resolved immediately. The amount of plastic waste in the city of Surabaya is one of the causes of damage to the environment. So that the plastic waste must be processed so that it can be reduced. Surabaya State University KKN students made this problem the basis for implementing the Socialization and Training of Plastic Waste Processing Types of LDPE (Low-Density Polypropylene) into Paving Blocks. The purpose of this activity is as an effort to reduce the amount of plastic waste and provide alternative new jobs for the community. This activity applies the lecture method, question and answer, simulation and practice. The action begins with the opening and filling out of the pre-test, then continues with filling in the material, making simulations, and the activity ends with closing and filling in the post-test. The pre-test and post-test assessments results showed that the participant's knowledge of the material was still classified as